Experimental investigation of the fluctuating static pressure in a subsonic axisymmetric jet. Issue 3 (June 2021) - Li, Songqi; Ukeiley, Lawrence S
Measuring the fluctuating static pressure within a jet has the potential to depict in-flow sources of the jet noise. In this work, the fluctuating static pressure of a subsonic axisymmetric jet was experimentally investigated using a 1/8" microphone with an aerodynamically shaped nose cone. The power spectra of the fluctuating pressure are found to follow the -7/3 scaling law at the jet centerline with the decay rate varying as the probe approaches the acoustic near field. Profiles of skewness and kurtosis reveal strong intermittency inside the jet shear layer. By applying a continuous wavelet transform (CWT), time-localized footprints of the acoustic sources were detected from the pressure fluctuations. To decompose the fluctuating pressure into the hydrodynamic component and its acoustic counterpart, two techniques based on the CWT are adopted. In the first method the hydrodynamic pressure is isolated by maximizing the correlation with the synchronously measured turbulent velocity, while the second method originates from the Gaussian nature of the acoustic pressure where the separation threshold is determined empirically. Similar results are obtained from both separation techniques, and each pressure component dominates a certain frequency band compared to the global spectrum. Furthermore, cross-spectra between the fluctuating pressure and the turbulent velocity were calculated, and spectral peaks appearing around Strouhal number of 0.4 are indicative of the footprint of the convecting coherent structures inside the jet mixing layer.